IMPACT OF COMPUTER VISION SYNDROME ON HEALTH OF COMPUTER USAGE BANK EMPLOYEE - RAMZAN, SHAHID; IRFAN, MOHAMMAD (IJRDO -Journal of Computer Science Engineering, 2016)
The computer has become a common item in today's society. Nearly 60 million people sufferfrom CVS globally and a million new cases occur each year. The aim to investigate theawareness and knowledge about Computer vision syndrome (CVS) among Bank employees.The sample of this study consisted 50 Bank employees. Both males and females bankemployees from private and public sector were selected. The Sample was randomly selected.The ages of Employees were 26 to 48. Self Prepared Questionnaire, Expert Reviewed and Pilotwere used to access the Objective. The results indicated that impact of Computer visionsyndrome on the health of human being who used the prolonged computer usage. Theinvestigator found a lot of the remedies and relieves from Computer vision syndrome wereas ; Blink more often (12-18/minute),Take breaks frequently (20-20-20 rule) after every 20minutes look at distant object at least 20 feet away for 20 seconds, Modify work place, Exercise& stretch eyes, Monitor display quality-choose a setting in which refresh rate and resolutionboth are high, Adjust the brightness of computer screen, Exercise even when sitting- stand up,move about or exercise arms, leg, back, neck, and shoulders frequently.